answerkey4_4

By applying the gauss-newton formula with the

Info iconThis preview shows pages 2–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: By applying the Gauss-Newton formula with the starting value 2, we can get the first and the second iterative value, x 1 and x 2 . Recall the Gauss-Newton formula is x n +1 = x n- f ( x n ) f 00 ( x n ) . With the condition x = 2, we have x 1 = x- f ( x ) f 00 ( x ) = 2- f (2) f 00 (2) = 0 . Next we plug in x 1 = 0 to the formula to get x 2 = 0- f (0) f 00 (0) = 4 / 5 . (b) (Ans) This time we chose a different starting value. Similarly we can get x 1 and x 2 from the iteration, now with x = 3. x 1 = x- f ( x ) f 00 ( x ) = 3- f (3) f 00 (3) = 5 x 2 = x 1- f ( x 1 ) f 00 ( x 1 ) = 5- f (5) f 00 (5) = 21 / 5 . (c) (Ans) Under some regularity conditions, we expect that x n will approach to the point x * at which the local minimum (or maximum) is obtained. To be precise, x n converges to x * where f ( x * ) = 0. To explain this, let us take the limit on each side of the Gauss-Newton formula. Then we have the equation, lim x n +1 = lim x n- lim f ( x n ) f 00 ( x n ) . Assuming the limit of the sequence { x n } exists (which we will denote as x * ), and f ( x ) and f 00 ( x ) are continuous. Then the above equation can be written as x * = x *- f ( x * ) f 00 ( x * ) . 2 Here we have used the fact that lim x n +1 = lim x n = x * , and lim g ( x n ) = g (lim x n ) for any continuous function g ( x ). Therefore, we conclude that f ( x * ) is zero. In this example, the Gauss-Newton optimization process pushes the sequence towards two different limits depending on starting value. The limit of x n is 1 with the initial value x = 2 however, x n converges to 4 with the initial value 3. The limit of { x n } can be sensitive to initial values especially when there are multiple solutions of x in the equation f ( x ) = 0 . We can tell the direction which { x n } converges to by looking at the signs of f ( x n ) and f 00 ( x n ). Let’s go back to our example. From the form of derivatives f ( x ) and f 00 ( x ), you will see that f ( x n ) > 0 and f 00 ( x n ) < 0 when x n < 1 . Therefore, f ( x n ) f 00 ( x n ) < 0 and thus we know from the Gauss-Newton formula that the next value in the sequence is larger than x n , i.e.,, i....
View Full Document

{[ snackBarMessage ]}

Page2 / 6

By applying the Gauss-Newton formula with the starting...

This preview shows document pages 2 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online